Relationships of Adrenoceptor Polymorphisms with Obesity - Kazuko Masuo; Gavin W. Lambert (Hindawi Limited, 2011)
Obesity, hypertension, and type 2 diabetes are rapidly growing public health problems. Heightened sympathetic nerve activity is a well-established observation in obesity, hypertension, and type 2 diabetes. Human obesity, hypertension, and diabetes have strong genetic as well as environmental determinants. Reduced energy expenditure and resting metabolic rate are predictive of weight gain, and the sympathetic nervous system participates in regulating energy balance through thermogenesis. The thermogenic effects of catecholamines in obesity are mainly mediated via the β2, and β3-adrenergic receptors in humans. Further, β2-adrenoceptors importantly influence vascular reactivity and may regulate blood pressure. β-adrenoceptor polymorphisms have also been associated with adrenoceptor desensitization, increased adiposity, insulin resistance, and enhanced sympathetic nervous activity. Many epidemiological studies have shown strong relationships between adrenoceptor polymorphisms and obesity, but the observations have been discordant. This paper will discuss the current topics involving the influence of the sympathetic nervous system and β2- and β3-adrenoceptor polymorphisms in obesity.